Book of Abstracts From 9th International Scientific Conference on Advances in Mechanical Engineering - Mihály Csüllög; Tamas Mankovits (Trans Tech Publications Ltd, 2023)
The 9th International Scientific Conference on Advances in Mechanical Engineering (ISCAME, November 9-10, 2023, Debrecen, Hungary) was organized by the Department of Mechanical Engineering (Faculty of Engineering, University of Debrecen) and the Working Commission of Mechanical Engineering (Specialized Committee in Engineering, Regional Committee in Debrecen, Hungarian Academy of Sciences). The main goal of ISCAME is to yearly bring together engineers, scientists, researchers, practitioners from academia and industry to present their original works and share experiences regarding all aspects of mechanical engineering sciences.